Naringenin prevents experimental liver fibrosis by blocking TGFβ-Smad3 and JNK-Smad3 pathways - Hernández-Aquino, Erika; Zarco, Natanael; Casas-Grajales, Sael; Ramos-Tovar, Erika; Flores-Beltrán, Rosa E; Arauz, Jonathan; Shibayama, Mineko; Favari, Liliana; Tsutsumi, Víctor; Segovia, José; Muriel, Pablo (World journal of gastroenterology : WJG, 2017)
AIM To study the molecular mechanisms involved in the hepatoprotective effects of naringenin(NAR)on carbon tetrachloride(CCl4)-induced liver fibrosis.METHODS Thirty-two male Wistar rats(120-150 g)were randomly divided into four groups:(1)a control group(n=8)that received 0.7%carboxy methyl-cellulose(NAR vehicle)1 m L/daily p.o.;(2)a CCl4 group(n=8)that received 400 mg of CCl4/kg body weight i.p.3 times a week for 8 wk;(3)a CCl4+NAR(n=8)group that received 400 mg of CCl4/kg body weight i.p.3times a week for 8 wk and 100 mg of NAR/kg body weight daily for 8 wk p.o.;and(4)an NAR group(n=8)that received 100 mg of NAR/kg body weight daily for 8 wk p.o.After the experimental period,animals were sacrificed under ketamine and xylazine anesthesia.Liver damage markers such as alanine aminotransferase(ALT),alkaline phosphatase(AP),γ-glutamyl transpeptidase(γ-GTP),reduced glutathione(GSH),glycogen content,lipid peroxidation(LPO)and collagen content were measured.The enzymatic activity of glutathione peroxidase(GPx)was assessed.Liver histopathology was performed utilizing Masson’s trichrome and hematoxylin-eosin stains.Zymography assays for MMP-9 and MMP-2 were carried out.Hepatic TGF-β,α-SMA,CTGF,Col-I,MMP-13,NF-κB,IL-1,IL-10,Smad7,Smad3,p Smad3 and p JNK proteins were detected via western blot.RESULTS NAR administration prevented increases in ALT,AP,γ-GTP,and GPx enzymatic activity;depletion of GSH and glycogen;and increases in LPO and collagen produced by chronic CCl4 intoxication(P<0.05).Liver histopathology showed a decrease in collagen deposition when rats received NAR in addition to CCl4.Although zymography assays showed that CCl4 produced an increase in MMP-9 and MMP-2gelatinase activity;interestingly,NAR administration was associated with normal MMP-9 and MMP-2 activity(P<0.05).The anti-inflammatory,antinecrotic and antifibrotic effects of NAR may be attributed to its ability to prevent NF-κB activation and the subsequent production of IL-1 and IL-10(P<0.05).NAR completely prevented the increase in TGF-β,α-SMA,CTGF,Col-1,and MMP-13 proteins compared with the CCl4-treated group(P<0.05).NAR prevented Smad3phosphorylation in the linker region by JNK since this flavonoid blocked this kinase(P<0.05).CONCLUSION NAR prevents CCl4 induced liver inflammation,necrosis and fibrosis,due to its antioxidant capacity as a free radical inhibitor and by inhibiting the NF-κB,TGF-β-Smad3 and JNK-Smad3 pathways.